Public support for a union default: Predicting factors and implications for public policy. (August 2022) - Harcourt, Mark; Gall, Gregor; Wilson, Margaret; Rubenstein, Korey; Shang, Sudong
Drawing on survey findings, in this article the authors examine levels of public support in New Zealand for a union default. The key findings are that support is high (59%), that support is principally predicted by a belief in the default's effectiveness for improving employees' lives, and that this belief mediates a number of other predictors, such as union membership, non-union by choice, political party, household income, gender and age. There are strong grounds for believing this would translate into actual support for a union default and a consequent rise in union membership. These findings are contextualised with regard to Australia, Britain, Canada and the United States, where the authors draw out the implications for public policy and how a union default could be operationalised in the countries under study.